Reframing Literacy in the Discipline of Science with the Disciplinary Literacy Observation Tool (DLOT). Issue 1 (16th November 2021) - Drew, Sally Valentino; Thomas, Jeffrey
Abstract: This article explains how teams of special educators, science teachers, literacy consultants, and administrators can use the Disciplinary Literacy Observation Tool (DLOT) and accompanying planning tool to improve disciplinary literacy instruction in inclusive secondary science classrooms. The DLOT was developed in partnership with practitioners as a tool for professional development and coaching. First, the tool's development and five dimensions are described: (a) aspects of disciplinary literacy in science, (b) instructional grouping, (c) student engagement, (d) quality of pedagogy, and (e) overall quality. Then, an illustration is provided for how special educators can collaborate with science educators and other colleagues to use the DLOT to identify, document, reflect upon, and set goals regarding disciplinary literacy instruction in science in ways that benefit students with learning disabilities. With the DLOT, practitioners can approach literacy integration in science to address both general and discipline‐specific strategies aligned synergistically to Common Core State Standards and Next Generation Science Standards through three‐dimensional science learning.